Keap1/Nrf2 impairing revised: are we missing the single nucleotide polymorphisms? - Muscarella, Lucia Anna; Fazio, Vito Michele (Journal of Thoracic Disease, 2016)
Oxidative stress represents one of the main causes of DNA damages in cancer development and it is mainly modulated by the Kelch-like ECH-associated protein 1 (Keap1)/Nuclear factor erythroid 2-related factor 2 (Nrf2) pathway that leads the mechanism of cellular adaptation to oxidative and xenobiotic stresses.